Exosome Mediated Delivery of miR-124 Promotes Neurogenesis after Ischemia - Jialei Yang; Xiufen Zhang; Xiangjie Chen; Lei Wang; Guodong Yang (Elsevier, 2017)
The intrinsic ability of neurogenesis after stroke has been proven weak, which results in insufficient repair of injury in the nerve system. Recent studies suggest multiple microRNAs (miRNAs) are involved in the neuroremodeling process. Targeted miRNAs delivery for amplification of neurogenesis is promising in promoting the prognosis after ischemia. Here, we showed that modified exosomes, with rabies virus glycoprotein (RVG) fused to exosomal protein lysosome-associated membrane glycoprotein 2b (Lamp2b), could efficiently deliver miR-124 to the infarct site. Systemic administration of RVG-exosomes loaded with miR-124 promoted cortical neural progenitors to obtain neuronal identity and protect against ischemic injury by robust cortical neurogenesis. Our study suggests that RVG-exosomes can be utilized therapeutically for the targeted delivery of gene drugs to the brain, thus having great potential for clinical applications.